Context-specific adaptation of an eHealth-facilitated, integrated care model and tailoring its implementation strategies—A mixed-methods study as a part of the SMILe implementation science project - Valenta, Sabine; Ribaut, Janette; Leppla, Lynn; Mielke, Juliane; Teynor, Alexandra; Koehly, Katharina; Gerull, Sabine; Grossmann, Florian; Witzig-Brändli, Verena; De Geest, Sabina, on behalf of the SMILe study team (Frontiers in Health Services, 2023)
Background. Contextually adapting complex interventions and tailoring their implementation strategies is key to a successful and sustainable implementation. While reporting guidelines for adaptations and tailoring exist, less is known about how to conduct context-specific adaptations of complex health care interventions. Aims. To describe in methodological terms how the merging of contextual analysis (CA) results (step 1) with the involvement of stakeholders and end-users, and considering overarching regulations (step 2) informed both our adaptation of an integrated care model (ICM) for SteM cell transplantatIon faciLitated by eHealth (SMILe-ICM) and our tailoring of its implementation strategies by following specific guidelines (step 3). Methods. Step 1: We used a mixed-methods design approach at University Hospital Basel, guided by the Basel Approach for coNtextual ANAlysis (BANANA). Step 2: Within an interdisciplinary clinical team (n=28), adaptations of the SMILe-ICM were discussed, with consideration for standard operating procedures (SOPs) and higher-level regulatory scenarios. Usability tests were conducted with patients (n=5) and clinicians (n=4). Step 3: SMILe–ICM adaptations were conducted by merging our results from steps 1 and 2 using the FRAME. We tailored the implementation strategies following ERIC compilation. Results. Step 1: Current clinical practice was mostly acute-care-driven. Patients and clinicians valued eICMs to support trustful patient-clinician relationships and the fitting of eHealth components to context-specific needs. Step 2: Based on information from project group meetings, adaptations are necessary on the organizational level (e.g., delivery of self-management information in in-patient settings). SOPs informed the tailoring of SMILe-ICM`s visit timepoints and content; data protection management was adapted following Swiss regulations; and steering group meetings supported infrastructure access. The usability tests informed further adaptation of technology components. Step 3: Following FRAME and ERIC, SMILe-ICM was contextually adapted and implementation strategies tailored to setting-specific needs. Discussion. This study provides context-driven guidance on how to conduct intervention adaptation including the tailoring of its implementation strategies. The revealed meso-level differences of the CA suggest a more targeted approach to enable an in-depth, informative adaptation process. A well-planned, theory-guided adaptation phase is an important first step and should be sufficiently incorporated and budgeted in every implementation science project.